Generalized stability criterion for exploiting optimized mechanical properties by a general correlation between phase transformations and plastic deformations. (December 2020) - Huang, Linke; Lin, Weitong; Zhang, Yubing; Feng, Dan; Li, Yujiao; Chen, Xiang; Niu, Kai; Liu, Feng
Abstract: Designing structured materials with optimized mechanical properties generally focuses on engineering microstructures, which are closely determined by the processing routes, such as phase transformations. However, the direct connection between phase transformations and mechanical properties remains largely unexplored. Here, we propose a new concept of generalized stability (GS) to correlate phase transformations with plastic deformations in terms of the trade-off relationship that exists between thermodynamics and kinetics. We then suggest that, to achieve structured materials with excellent strength–plasticity combinations, phase transformations and/or plastic deformations with high GS, thermodynamic driving force (Δ G ), and kinetic activation energy ( Q ), are highly expected. We verify the GS concept against a phase transformation-modulated nanostructured Fe alloy, for which an ultrahigh yield strength of 2.61 GPa and an ultimate compressive strength of 3.32 GPa while having a total strain to failure of 35% are achieved via multiple strengthening and hardening mechanisms. A theoretical analysis, in combination with microstructural characterization, indicates that the desired thermo-kinetic parameter triplets (i.e., high GS-high Δ G -high Q ) could be inherited from the phase transformation to the plastic deformation, which ultimately yields good mechanical performance. The proposed concept can be regarded as the first theoretical criterion or a general rule that correlates phase transformation with plastic deformation, and can assist in the rapid selection of phase transformations to facilitate superior mechanical properties. Graphical abstract: Image, graphical abstract